Ideal Cardiovascular Health in Racially and Ethnically Diverse People with Serious Mental Illness - Hawes, Mark R. (J Health Care Poor Underserved, 2020)
Cardiovascular disease is a primary contributor to premature death among people with serious mental illness (SMI). This study used baseline data (N=314) from an effectiveness trial testing a healthy lifestyle intervention for racial/ethnically diverse participants with overweight/obesity and SMI living in supportive housing. We examined the prevalence and correlates of a modified version of the American Heart Association (AHA) metric of ideal cardiovascular health (ICVH). Five AHA ICVH metrics (smoking, body mass index, diet, physical activity, and blood pressure) were used to create a composite ICVH score. The mean ICVH score was 3.15 (range 0 – 8). Multivariate analysis indicated that higher ICVH scores were associated with lifetime cancer diagnosis and better cardiorespiratory fitness. Lower scores were associated with female gender, racial/ethnic minority status, and antipsychotic use suggesting that these subgroups may benefit from targeted screening and interventions to improve cardiovascular health in people with SMI.